Penggunaan Metode Simple Additive Weighting dalam Aplikasi Mobile untuk Proses E-Recruitment - Tommy; Ari Usman (Journal of Informatics Management and Information Technology, 2024)
E-Recruitment is internet-based employee recruitment that is carried out by many companies today. In the research that the author conducted, recruitment was completed with decision support selection using SAW. The SAW method produces ranking output against alternatives. The alternative with the highest value is the best. In this system the alternative in question is the applicant. When registering, applicants are required to input data, including the attribute data required for selection using the SAW method. With this system, it is hoped that recruitment will be easy and practical at the initial selection stage. From this research, the results of selection using the SAW method are a ranking of scores from highest to lowest and information on whether an applicant's application is accepted or rejected can be seen through the applicant's application easily and the weight for each criterion can be changed according to the company's request